IMPLEMENTASI AJARAN TRI HITA KARANA PADA PELESTARIAN LEMBU PUTIH DI DESA TARO - Ida Ayu Dwidyaniti Wira (Dharma Duta, 2020)
Ceremony (Ritual) is the basic framework of Hinduism, which is in the form of materialistic offerings and also contains non-material elements. The ceremony is made through the concepts of Tattwa and Jnana, based on the intention of offering through the teachings of Catur Marga, namely: Karma Marga, Bakti Marga, Jnana Marga and Raja Yoga. Rituals are a procession of offerings that are organized by realizing ceremonies and events that have the aim of building morality based on morality which is implemented in ethics which will have a positive impact to get closer to God Almighty. The Hindu worship system has three dimensions, namely the application of the Tri Hita Karana Teachings. In connection with the teachings of Tri Hita Karana, the preservation of the White Ox in Taro Village is an implementation of the teachings of Tri Hita Karana itself. This study used a qualitative design. Data were collected using the observation method, interview method, library method and documentation method. Based on this analysis, the following research results were obtained: (1) The relationship between the preservation of white cattle and Parhyangan, namely: a) The relationship between preservation of white cattle and mamineh empehan in Taro Village; b) The relationship between the preservation of white cattle and the mepada ceremony in Taro Village; c) The relationship between preserving white oxen at the Tawur Panca Wali Krama Agung ceremony in Taro Village. (2) The relationship between the preservation of white cattle and Pawongan, namely: a) The relationship between the preservation of white cattle and breeders in Taro Village; b) The relationship between the preservation of white cattle and the Taro Village Community. (3) The relationship between the preservation of white cattle and Palemahan, namely: a) White cow dung is related to environmental sustainability in Taro Village; b) The relationship between the preservation of white cattle and the Tourism Park; c) The relationship between the preservation of white cattle and flora and fauna.